Contextualizing secession normative studies in comparative perspective - Coppieters, Bruno; Sakwa, Richard; Oxford eBooks (Oxford : Oxford University Press, 2003)
On the basis of ten case studies, this book provides a combination of research with fundamental questions about why states stay together, and above all why sometimes they fall apart.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Secession -- Case studies; Self-determination, National -- Case studies; Separatist movements -- Case studies; Electronic books